(untitled) (Asian Education Studies, 2016)
This study seeks to present through a case study a new phenomenon that is still limited in scope, but is taking shape within the Israeli education system. It is that of Muslim Arab women who choose to teach in Israeli Jewish schools. The article presents the case study of such a teacher. The purpose of the article is to analyze the subject’s perceptions, beliefs and feelings in the context of her place within the Israeli education system and the understanding of the mechanisms she employs to reinforce her sense of self-efficacy in coping with the identity conflict deriving from being an Arab teacher in a Jewish high school. The study is interpretative in nature and examines how the Muslim Arab teacher perceives her integration while relating to the experiences with various bodies (administration, colleagues, students and parents). The study is based on an open in-depth interview with the teacher. Findings indicated how tools relating to her personal sense of self-efficacy help her bridge the gap between her professional and personal identities.